Ecological Welfare State: Rekonstruksi Tanggung Jawab Negara dalam Pemenuhan Hak Atas Lingkungan Hidup yang Baik dan Sehat - Muhammad Kamil Ridha; Eny Kusdarini; Roul Alvaro Prasetyo (Legalita, 2026)
This research is situated within the intersection of constitutional law and environmental policy, focusing on the paradigm shift toward an ecological welfare state. The primary objective is to reconstruct the scope of state responsibility in fulfilling the fundamental right to a healthy environment. The topic is selected in response to the urgent need to address the global ecological crisis, which is largely driven by traditional welfare models that often prioritize industrial and economic growth over environmental sustainability. Employing a normative legal research methodology with conceptual and statutory approaches, this study examines the transformation from a conventional welfare state to one centered on ecological integrity. The research argues that state responsibility must be reformulated to integrate ecological limits as a core constitutional mandate rather than a scondary policy concern. Findings reveal that while Indonesia’s “Green Constitution” provides a solid foundational framework, significant juridical and political challenges such as inconsistent regulations and developmentalist biases, hinder its effective implementation. These obstacles necessitate the deployment of comprehensive legal and economic instruments to operationalize ecological welfare principles. Furthermore, the study identifies ecological citizenship, specifically within the context of civic education, as a critical dimension for fostering public participation and environmental stewardship. This study contributes to the field of environmental constitutionalism by providing a theoretical and practical framework for greening state functions. Ultimately, it emphasizes that the legitimacy of a modern legal state depends on its capacity to ensure ecological sustainability as a prerequisite for social and economic welfare.